2021
DOI: 10.3892/br.2021.1471
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of the influence of Epigallocatechin gallate on Sjögren's syndrome associated molecular regulators of exocytosis (Review)

Abstract: Sjögren's syndrome (SS) is an autoimmune disorder that affects the salivary glands, leading to reduced secretory functions and oral and ocular dryness. The salivary glands are composed of acinar cells that are responsible for the secretion and production of secretory granules, which contain salivary components, such as amylase, mucins and immunoglobulins. This secretion process involves secretory vesicle trafficking, docking, priming and membrane fusion. A failure during any of the steps in exocytosis in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 134 publications
(204 reference statements)
0
3
0
Order By: Relevance
“…For the EORTC QLQ-OES18 scale, the analysis found that postoperative tea consumption improved signi cantly on eating problems, odynophagia, trouble swallowing saliva, coughing and speech problems. The main mechanism may be through the antioxidant and anti-in ammatory effects of Ltheanine (Chen et al 2022a) and epigallocatechin (Errachid et al 2021) components in tea to achieve improve pain and maintain a stable oral environment. This suggests that cancer patients may improve their oral environment and thus symptoms such as di culty eating, dry mouth, cough and swallowing by drinking tea.…”
Section: Discussionmentioning
confidence: 99%
“…For the EORTC QLQ-OES18 scale, the analysis found that postoperative tea consumption improved signi cantly on eating problems, odynophagia, trouble swallowing saliva, coughing and speech problems. The main mechanism may be through the antioxidant and anti-in ammatory effects of Ltheanine (Chen et al 2022a) and epigallocatechin (Errachid et al 2021) components in tea to achieve improve pain and maintain a stable oral environment. This suggests that cancer patients may improve their oral environment and thus symptoms such as di culty eating, dry mouth, cough and swallowing by drinking tea.…”
Section: Discussionmentioning
confidence: 99%
“…For the EORTC QLQ-OES18 scale, the analysis found that postoperative tea consumption improved significantly on eating problems, odynophagia, trouble swallowing saliva, coughing and speech problems. The main mechanism may be through the antioxidant and antiinflammatory effects of L-theanine [24] and epigallocatechin [25] components in tea to achieve improve pain and maintain a stable oral environment. This suggests that cancer patients may improve their oral environment and thus symptoms such as difficulty eating, dry mouth, cough and swallowing by drinking tea.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of β1-adrenergic receptor induces exocytosis of protein storage granules via the cAMP/PKA pathway [ 38 ]. During exocytosis, SNARE proteins play a crucial role in membrane trafficking and fusion [ 48 ]. Mucins, primarily MUC5B and MUC7 in human saliva, are the major proteins released through exocytosis [ 49 ].…”
Section: Physiology Of Saliva Secretionmentioning
confidence: 99%